SURFACE SOLID DISPERSION OF MORINGA OLEIFERA LEAF EXTRACT-MICROCRYSTALLINE CELLULOSE PH 102-POLOXAMER 188: PREPARATION AND CHARACTERIZATION - RANI, KARINA C.; NAWATILA, ROISAH; NATASYA, ZULVIARA PD; ANGELA, VERONIKA G.; WANTI, WINDA M; JAYANI, NIKMATUL IE (International Journal of Applied Pharmaceutics, 2024)
Objective: The development of pharmaceutical products containing Moringa oleifera leaf extract has not developed well due to the physical and chemical characteristics limitations. The development of Surface Solid Dispersion (SSD) of Moringa oleifera leaves extract-microcrystalline cellulose PH102-Poloxamer 188 with 1:2:0.5 and 1:4:0.5 was performed in this study to improve the physicochemical characteristics of this extract. Methods: SSD were prepared by microwave irradiation method using 400 W of power and 3 min of time exposure. The prepared SSD were evaluated for flowability, compressibility, moisture content, thermal characteristics (Differential Scanning Calorimetry (DSC)), crystallinity (Powder X-ray Diffractometry (PXRD)), functional group interaction (Fourier Transform Infra-Red Spectroscopy (FT-IR)), morphology (Scanning Electron Microscopy (SEM)), total flavonoid content, solubility study, and antioxidant activity. Results: SSD powder exhibited better flowability, compressibility, and moisture content compared to the physical mixture (PM). The results of thermal characteristics and crystallinity of SSD indicate partial transformation into an amorphous phase. The total flavonoid content of SSD 1:2:0.5 was 11.04±0.23 mg QE/g, whereas SSD 1:4:0.5 was 9.18±0.05 mg QE/g. The solubility of the flavonoid compound from SSD 1:2:0.5 (78.73±0.76 µg/ml) and SSD 1:4:0.5 (61.90±3.38 µg/ml) was higher than PM with the equal ratio. The antioxidant activity was expressed as IC50 values of SSD, which are 276.72±24.18 ppm for a 1:2:0.5 ratio and 249.04±27.29 ppm for a 1:4:0.5 ratio. Conclusion: SSD preparation successfully improved the physicochemical characteristics and solubility of Moringa oleifera leaf extract. SSD 1:2:0.5 was the optimized composition from this study.